An efficient and hydrophobic molecular doping in perovskite solar cells. (April 2021) - Luo, Junsheng; Lin, Fangyan; Xia, Jianxing; Yang, Hua; Zhang, Ruilin; Malik, Haseeb Ashraf; Shu, Hongyu; Wan, Zhongquan; Han, Keli; Wang, Ruilin; Yao, Xiaojun; Jia, Chunyang
Abstract: Longevity has been a long-standing challenge for perovskite photovoltaics. In general, Li-TFSI/ t -BP are the state-of-the-art bi-dopants for the hole-transporting layer (HTL) in perovskite solar cells (PSCs), although such dopants significantly diminish the stability of devices. Here, we reported a novel dopant of fluorinated iron(III) porphine (Fe(III)-PP) as a potential alternative to the Li-TFSI/ t -BP. The optimized PSCs exhibit a champion power conversion efficiency (PCE) of 21.73%, which outperforms the standard bi-dopants Li-TFSI/ t -BP (21.07%). The high migration barrier together with the hydrophobic nature of the Fe(III)-PP, which in turn suppress intrinsic ion migration and alleviate extrinsic moisture-induced degradation, resulting in prominent improvement of long-term stability of PSCs up to 1200 h under air exposure without encapsulation. Graphical Abstract: ga1 Highlights: A novel dopant fluorinated iron(III) porphine (Fe(III)-PP) has been developed for PTAA in PSCs. Fe(III)-PP has excellent doping performance, high migration barrier and hydrophobic nature. PSCs based on Fe(III)-PP doped PTAA show a champion efficiency as high as 21.73%. PSCs exhibit superior long-term stability up to 1200 h under air exposure without encapsulation.